The role of access to finance for smallholders' seed business growth in Nepal. Issue 2 (17th February 2021) - Choudhary, Dyutiman; Banskota, Kamal; Khanal, Narayan; Gyawali, Prithvi
ABSTRACT: Finance is vital for commercialising seed businesses and the Government of Nepal has launched a priority sector-lending plan (PSLP) for financing agriculture. This article assesses the use and role of finance and the challenges in accessing PSLP loans, using interviews with 197 farmer households and stakeholders. The results show that awareness about PSLP can increase gross margins by 46%, but farmers have yet to take on PSLP loans. Bankers lack the agribusiness knowledge to support PSLP. The study recommends that policymakers and bankers harmonise policies and PSLP implementation by aligning loans with cropping cycles, farmers' institutions, seed value chains and effective outreach.